2012
DOI: 10.1371/journal.pone.0039836
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Treatment Reduces Cardiac Progenitor Cell Dysfunction and Prevents Morpho-Functional Ventricular Remodeling in Type-1 Diabetic Rats

Abstract: Emerging evidence suggests that both adult cardiac cell and the cardiac stem/progenitor cell (CSPC) compartments are involved in the patho-physiology of diabetic cardiomyopathy (DCM). We evaluated whether early administration of Resveratrol, a natural antioxidant polyphenolic compound, in addition to improving cardiomyocyte function, exerts a protective role on (i) the progenitor cell pool, and (ii) the myocardial environment and its impact on CSPCs, positively interfering with the onset of DCM phenotype. Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 54 publications
6
65
0
Order By: Relevance
“…In another study, resveratrol treatment has been shown to normalize free fatty acid oxidation, enhance glucose utilization, and reduce biomarkers of oxidative stress in the hearts of streptozocin-induced diabetic rats [242]. Similarly, resveratrol treatment was found to improve the cardiac function in streptozocin-induced type 1 diabetic rats, at least in part, through preserving the functional abilities of cardiac stem/progenitor cells [249]. Moreover, in streptozocin-induced diabetic mice, both low (60 mg/kg/day) and high (300 mg/kg/day) dose resveratrol treatment improved cardiac function, ameliorated oxidative injury, and reduced apoptosis in the hearts of treated diabetic mice [250].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…In another study, resveratrol treatment has been shown to normalize free fatty acid oxidation, enhance glucose utilization, and reduce biomarkers of oxidative stress in the hearts of streptozocin-induced diabetic rats [242]. Similarly, resveratrol treatment was found to improve the cardiac function in streptozocin-induced type 1 diabetic rats, at least in part, through preserving the functional abilities of cardiac stem/progenitor cells [249]. Moreover, in streptozocin-induced diabetic mice, both low (60 mg/kg/day) and high (300 mg/kg/day) dose resveratrol treatment improved cardiac function, ameliorated oxidative injury, and reduced apoptosis in the hearts of treated diabetic mice [250].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…T1D contractile dysfunction is characterized by a decrease in fractional shortening [17,18], ejection fraction [19], and heart rate [20]. However, unlike other heart failure models, they do not always develop cardiac hypertrophy [20,21], heart weight change [18,22] or cardiac atrophy [23]. This particularity is possibly due to apoptosis [24] and/or depression of cardiomyocyte volume [25].…”
Section: Ca 2+ Signaling In Type 1 Diabetesmentioning
confidence: 99%
“…Apart from that, Zhang et al [9] have shown that treatment with resveratrol (20 mg/kg/day orally for 4 weeks) improves left ventricular (LV) diastolic relaxation by inhibiting oxidative/nitrosative stress. A very recent study has shown that 8 weeks treatment with resveratrol (2.5 mg/kg/day; IP) improves diabetic heart function through reducing ventricular inflammation and remodeling [10]. In another recent study it has been shown that resveratrol given at 2.5 mg/ /kg/day orally for 4 weeks prevented from cardiac and vascular dysfunction in diabetic rats through its effect on redox balance [5].…”
Section: Introductionmentioning
confidence: 99%